Student's attitudes towards the implementation of collaborative brainstorming as a pre-writing activity - Marcos, Haykal Kaciepi; Safitri, Dian (Journal of English Language Teaching, 2025)
This study aimed to find how Essay Writing class Students at Universitas Negeri Padang's attitudes towards the implementation of collaborative brainstorming as a pre-writing activity. This study employed a quantitative method to collect data and was a descriptive study using a 4-point Likert scale questionnaire with 22 statements: 1 (strongly disagree), 2 (disagree), 3 (neutral), 4 (agree), and 5 (strongly agree). The sample included 28 students who had experienced a collaborative brainstorming activity in their essay writing class. The findings indicate that students generally hold a positive attitude toward the activity. The highest mean score was in the "Negotiated Decision-Making" and “Share Responsibility” indicator (3.30), categorized as very positive. The "Shared Decision-Making" (3.29). Overall, the results suggest that students view collaborative brainstorming activity as a beneficial and effective pre-writing stage.